Diagnostic performance of multi-branch coronary angiography-based index of microcirculatory resistance: a novel approach - Fan, Yongzhen; Wang, Shuang; Cai, Xinyong; Hu, Xiaorong; Ma, Jun; Lan, Hongzhi; Lu, Zhibing (Frontiers in Medicine, 2025)
BackgroundWire-based index of microcirculatory resistance (IMR) utilizing pressure wires and thermodilution techniques for the assessment of coronary microcirculatory function, presents challenges for clinical routine use due to its complexity, time-consuming, and costly. This study introduces a novel multi-branch and wire-free method for IMR calculation based on coronary angiography. The diagnostic performance of CAG-IMR is validated within a retrospective single-center investigation.MethodsIn a retrospective single-center study, 139 patients with 201 vessels were evaluated using CAG-IMR for coronary microvascular dysfunction (CMD) detection, utilizing wire-based IMR as the reference standard. CMD was determined based on wire-based IMR ≥25U. CAG-IMR was independently calculated from diagnostic coronary angiography in a blinded fashion, employing the same diagnostic threshold of 25U for CMD identification.ResultsCAG-IMR demonstrated significant correlation (r = 0.84, p < 0.001) and good diagnostic performance AUC = 0.97 (95% CI: 0.95–0.99) compared to wire-based IMR. It exhibited the overall diagnostic accuracy at 95.0% (95% CI: 92.0%−98.0%), alongside high sensitivity (92.7%) and specificity (95.6%). The positive predictive value (PPV) stood at 84.4%, and the negative predictive value (NPV) reached 98.1%.ConclusionsThis study introduces CAG-IMR, a novel, multi-branch and wire-free method for IMR calculation. The indicator demonstrates good diagnostic accuracy and correlation with wire-based IMR in a cohort of 139 patients and 201 vessels, with the potential to enhance clinical CMD assessment.